2006
DOI: 10.1128/jb.00959-06
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative and Critical Roles for Both G Domains in the GTPase Activity and Cellular Function of Ribosome-Associated Escherichia coli EngA

Abstract: To probe the cellular phenotype and biochemical function associated with the G domains of Escherichia coli EngA (YfgK, Der), mutations were created in the phosphate binding loop of each. Neither an S16A nor an S217A variant of G domain 1 or 2, respectively, was able to support growth of an engA conditional null. Polysome profiles of EngA-depleted cells were significantly altered, and His 6 -EngA was found to cofractionate with the 50S ribosomal subunit. The variants were unable to complement the abnormal polys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
87
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 27 publications
12
87
2
Order By: Relevance
“…The DrhlE derivative was used to reduce competition from endogenous RhlE; however, similar results were obtained when these experiments were performed in the MG1655 background (data not shown). Cells were analyzed by ultracentrifugation in buffer containing 100 mM NH 4 Cl and 10 mM MgCl 2 , similar to conditions that have been used to analyze the association of assembly factors with the ribosome (Sato et al 2005;Bharat et al 2006;Hwang and Inouye 2006). Western blot analysis of the individual fractions indicated that the majority of tagged RhlE (molecular weight=53 kDa) were found in fractions 4 and 5.…”
Section: Rhle Is a Ribosome-associated Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The DrhlE derivative was used to reduce competition from endogenous RhlE; however, similar results were obtained when these experiments were performed in the MG1655 background (data not shown). Cells were analyzed by ultracentrifugation in buffer containing 100 mM NH 4 Cl and 10 mM MgCl 2 , similar to conditions that have been used to analyze the association of assembly factors with the ribosome (Sato et al 2005;Bharat et al 2006;Hwang and Inouye 2006). Western blot analysis of the individual fractions indicated that the majority of tagged RhlE (molecular weight=53 kDa) were found in fractions 4 and 5.…”
Section: Rhle Is a Ribosome-associated Factormentioning
confidence: 99%
“…Studies in Saccharomyces cerevisiae have suggested that nearly 200 proteins function as ribosome assembly factors (Venema and Tollervey 1999;Harnpicharnchai et al 2001;Grandi et al 2002;Saveanu et al 2003). In contrast, only 10-15 assembly factors have been identified in E. coli (Alix and Guerin 1993;Bylund et al 1998;El Hage et al 2001;Charollais et al 2003Charollais et al , 2004Inoue et al 2003;Gutgsell et al 2005;Bharat et al 2006;Hwang and Inouye 2006;Jiang et al 2006), suggesting either a lower degree of ribosomal complexity in prokaryotes, or that additional ribosome assembly factors remain to be discovered (FromontRacine et al 2003;Hage and Tollervey 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these GTPases, bacteria also encode additional GTPases involved in 50S assembly: YihA and EngA (Der). 46,50,51 In bacteria, depletion of these GTPases leads to the accumulation of distinct intermediates, which are stable in sucrose gradients and can be purified and analyzed for their protein content. The intermediate observed upon YihA depletion has a slightly slower sedimentation rate than the 45S intermediates observed when RbgA and EngA are depleted.…”
Section: Gtpases Constitute a Large And Diverse Class Of Ribosome Assmentioning
confidence: 99%
“…In general, these proteins were discovered through conventional genetic approaches or were predicted on the basis of their similarity to other ribosome-associated proteins. These proteins include GTPases, methyltransferases, pseudouridine synthases, RNA helicases, chaperones, and proteins with unknown function (1,6,9,12,13,19,27,28,31,51,54). Additional ribosome-associated proteins can be predicted from a relatively recent high-throughput protein complex interaction study in E. coli that yielded a list of proteins that copurify either with ribosomal proteins or with known ribosome assembly factors (10).…”
mentioning
confidence: 99%